(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of undernutrition and overweight/obesity, and to assess their associations with clinical, paraclinical features and length of hospital stay among pediatric patients with acute pancreatitis (AP) at Children’s Hospital 2 (CH2), Ho Chi Minh City. Methods: A cross-sectional study was conducted on 155 pediatric patients diagnosed with acute pancreatitis and treated at the Hepatobiliary Pancreatic Department, Children’s Hospital 2, from April 2022 to April 2025. Results: The prevalence of undernutrition was 23.2%, including stunting (11%), wasting (10.3%), and underweight (1.9%). The rates of overweight and obesity were 12.9% and 16.8%, respectively. Factors associated with undernutrition included the etiology of AP and length of hospital stay. Children with identified causes of AP had a higher risk of undernutrition compared to idiopathic cases (PR = 2.37; 95% CI: 1.22–4.59; p = 0.006), had a lower risk of overweight/obesity compared to those with idiopathic acute pancreatitis (PR = 0.48; 95% CI: 0.25–0.81). Each additional day of hospitalization increased the risk of undernutrition (PR = 1.05; 95% CI: 1.00–1.10; p = 0.003). Children who developed complications had a higher risk of overweight/obesity than those without complications (PR = 1.66; p = 0.039). Children who did not undergo surgery had a 4.65 times higher prevalence of overweight/obesity compared to those who received surgical intervention (95% CI: 1.52–14.2). Conclusion: The prevalence of overweight and obesity in AP were high and associated with AP etiology, complications, and surgical interventions Undernutrition was associated with the etiology of AP and the length of hospital stay. Nutritional care is needed to reduce malnutrition in children with acute pancreatitis, and larger sample size studies are required to determine the association between overweight, obesity, and the causes and progression of acute pancreatitis in children.